Patient‐identified impact of symptoms in spinal and bulbar muscular atrophy. Issue 1 (25th September 2017) - Guber, Robert D.; Kokkinis, Angela D.; Schindler, Alice B.; Bendixen, Roxanna M.; Heatwole, Chad R.; Fischbeck, Kenneth H.; Grunseich, Christopher
ABSTRACT: Introduction : The effects of spinal bulbar muscular atrophy (SBMA) on quality of life (QoL) are not well understood. This study describes symptoms from the patient's perspective and the impact these symptoms have on QoL. Methods : We conducted open‐ended interviews with 21 adult men with genetically confirmed SBMA. Using a qualitative framework technique, we coded and analyzed interviews to identify symptoms and resulting themes. Results : From these interviews, 729 quotations were extracted. We identified 200 SBMA‐specific symptoms and 20 symptomatic themes. Weakness was mentioned by all interviewees. Symptoms within the domain of mental health and the specific themes of emotional issues and psychological impact were also frequently mentioned. Discussion : Numerous symptoms affect QoL for patients with SBMA. We identified previously unrecognized symptoms that are important to address in enhancing clinical care for patients with SBMA and in developing tools to evaluate efficacy in future clinical trials. Muscle Nerve 57 : 40–44, 2018